Ultrasound-Guided Proximolateral Approach for Digital Flexor Tendon Sheath Injection in the Horse: A Cadaver Study - Horne, Caitlyn R.; Redding, William R.; Ru, Hongyu; Schnabel, Lauren V. (VCOT Open, 2019)
Objectives The aim of this study was to define a reliable ultrasound-guided proximolateral approach (PLA) for injection of the digital flexor tendon sheath (DFTS) in horses that would be as accurate as the landmark-guided basilar sesamoidean approach (BSA).Study Design Forty cadaveric limbs with no palpable effusion or DFTS abnormalities were randomly and evenly distributed between one senior (WRR) and one resident clinician (CRH) and between ultrasound-guided PLA and landmark-guided BSA groups. Limbs were injected with contrast, radiographed, and dissected. For each injection, the following was recorded: clinician, order of injection, number of attempts, if contrast was present within the DFTS, and if a structure other than the DFTS was penetrated.Results The ultrasound-guided PLA resulted in a greater number of successful injections into the DFTS than the landmark-guided BSA (19/20 vs. 16/20, respectively) with significantly fewer attempts (p = 0.03). The ultrasound-guided PLA also resulted in significantly less penetration of the surrounding soft tissue structures compared with the landmark-guided BSA (p = 0.02). Neither clinician experience nor injection number within the series was determined to have an effect on injection outcome.Conclusions The ultrasound-guided PLA to the DFTS is accurate and technically easy to perform. This approach should be considered for synoviocentesis of the DFTS, particularly in cases in which effusion is not present to reduce soft tissue trauma.
Keywords: horse; digital flexor tendon sheath; ultrasound-guided injection; landmark-guided injection; interventional ultrasound